2019
DOI: 10.1128/aac.00461-19
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of New Delhi Metallo-β-Lactamase (NDM) Using Tryptic Peptides and LC-MS/MS

Abstract: There is significant interest in the development of mass spectrometry (MS) methods for antimicrobial resistance protein detection, given the ability of these methods to confirm protein expression. In this work, we studied the performance of a liquid chromatography, tandem MS multiple-reaction monitoring (LC-MS/MS MRM) method for the direct detection of the New Delhi metallo-β-lactamase (NDM) carbapenemase in clinical isolates. Using a genoproteomic approach, we selected three unique peptides (SLGNLGDADTEHYAASA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In theory, a future combination of both applications could result in an all-in-one diagnostic tool for the identification of bacteria and determination of resistance mechanisms. While the ability of targeted LC-MS/MS to accurately and rapidly identify several resistance mechanisms in bacterial subcultures has been demonstrated in previous studies ( Charretier et al, 2015a , b ; Hassing et al, 2016 ; Wang et al, 2017 , 2019a , b ; Cecchini et al, 2018 ; Foudraine et al, 2019 ; Strich et al, 2019 ), to our knowledge, no studies have demonstrated its use for the direct detection of resistance mechanisms in positive blood cultures. Furthermore, most studies focused on a limited number of AMR mechanisms, and not on the prediction of AMR in prospectively collected cultures.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In theory, a future combination of both applications could result in an all-in-one diagnostic tool for the identification of bacteria and determination of resistance mechanisms. While the ability of targeted LC-MS/MS to accurately and rapidly identify several resistance mechanisms in bacterial subcultures has been demonstrated in previous studies ( Charretier et al, 2015a , b ; Hassing et al, 2016 ; Wang et al, 2017 , 2019a , b ; Cecchini et al, 2018 ; Foudraine et al, 2019 ; Strich et al, 2019 ), to our knowledge, no studies have demonstrated its use for the direct detection of resistance mechanisms in positive blood cultures. Furthermore, most studies focused on a limited number of AMR mechanisms, and not on the prediction of AMR in prospectively collected cultures.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, by detecting conserved peptides, many protein variants of resistance mechanisms can be detected using single targets ( Welker and van Belkum, 2019 ). In several studies, targeted LC-MS/MS assays were developed for the detection of specific resistance mechanisms such as small-spectrum β-lactamases ( Cecchini et al, 2018 ), carbapenemases ( Wang et al, 2017 , 2019b ; Cecchini et al, 2018 ; Foudraine et al, 2019 ; Strich et al, 2019 ), PBP2a and PBP2c ( Charretier et al, 2015a ), AmpC β-lactamases ( Charretier et al, 2015b ), efflux pumps ( Charretier et al, 2015b ; Cecchini et al, 2018 ), alterations in the quinolone resistance determining region (QRDR) of GyrA ( Hassing et al, 2016 ), MCR-1 ( Wang et al, 2019a ), and aminoglycoside resistance mechanisms ( Foudraine et al, 2021a ). However, the potential of targeted LC-MS/MS to detect resistance mechanisms directly in positive blood cultures has to our knowledge not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Specific peptides of A. baumannii identified via LC-MS/MS profiling have been used to classify clinical isolates ( Honghui et al, 2016 ). Targeted high-resolution MS assays have been developed for the detection of KPC, OXA-48, NDM, and VIM enzymes ( Wang et al, 2017 , 2019 ; Foudraine et al, 2019 ; Strich et al, 2019 ). However, there are still many β-lactamases that have not been detected by targeted proteomics.…”
Section: Introductionmentioning
confidence: 99%
“…The potential applications of this method depend on the specificity and strength of the antigen–antibody reaction being evaluated. Due to the limitation of ELISAs requiring the use of a purified antigen and an extraordinarily functional antibody, some researchers strongly propose that other methods be used, such as liquid chromatography–mass spectrometry (LC-MS) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] and various lab-on-a-chip methods [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. A recent trend in LC-MS development for diagnosis is to focus on the detection of drugs and biomarkers, including peptides and steroids, owing to difficulties in preparing suitable antibodies against these small molecules, whereas lab-on-a-chip–based platforms are thought to offer easier sample preparation, chemical manipulation and reaction, and high throughput using various novel detection techniques with, sometimes, label-free detection.…”
Section: Introductionmentioning
confidence: 99%